Perancangan Optimalisasi Pengendalian Intern atas Pelaporan Keuangan (PIPK) pada Proses Pengelolaan Barang Rampasan KPK - Firdha Maghfira; Ludovicus Sensi Wondabio (Postgraduate Program Merdeka University, 2023)
This study aims to improve the design of Internal Control over Financial Reporting(ICoFR) for the Corruption Eradication Commission (CEC)'s booty management processbased on policies and best practices from various references related to Internal Controlover Financial Reporting (ICoFR) for the public sector in Indonesia. The improvementsof the ICoFR design was carried out through a qualitative research approach in the formof a single case study, using primary data obtained from direct interviews and secondarydata in the form of documentation instruments. The research data was then carried out byqualitative descriptive analysis and content analysis, and the validity of the data wastested using data source and method triangulation. The results of this study are in the formof initial drafts of ICoFR designs, initial drafts of formal guidelines for IcoFRimplementations, and initial drafts of policies to encourage ICoFR improvements in theCEC's booty management process.DOI: https://doi.org/10.26905/afr.v6i3.10285